GENERAL AGREEMENT ON TRADE AND TARIFFS, ASEAN ECONOMIC COMMUNITY AND THE OMNIBUS LAW: IMPLICATIONS FOR INDONESIA'S COFFEE EXPORT AND IMPORT POSITION IN ASEAN - Budiman; Aang Kusmawan (UIN Sunan Gunung Djati Bandung, 2025)
Indonesia is a member of the World Trade Organization (WTO). After joining the WTO, Indonesia has continued to develop various international trade schemes with a number of countries. This article attempts to analyze the dynamics of Indonesia's coffee exports and imports through a supply and demand theory approach. Statistical data is used to analyze the current dynamics of Indonesia's coffee exports and imports. The results of the study show that to boost coffee exports and imports in ASEAN, Indonesia has issued a number of tariff exemption regulations. However, the value of Indonesia's exports and imports still lags far behind Vietnam's. The main issue with Indonesia's coffee production is the low productivity and comparative advantage of its coffee products.